Indirectly measuring evaluations of several attitude objects in relation to a neutral reference point - Brendl, C. Miguel; Markman, Arthur B.; Messner, Claude (Journal of experimental social psychology, 2005)
This article presents a new response time measure of evaluations, the Evaluative Movement Assessment (EMA). Two properties are verified for the first time in a response time measure: (a) mapping of multiple attitude objects to a single scale, and (b) centering that scale around a neutral point. Property (a) has implications when self-report and response time measures of attitudes have a low correlation. A study using EMA as an indirect measure revealed a low correlation with self-reported attitudes when the correlation reflected between-subjects differences in preferences for one attitude object to a second. Previously this result may have been interpreted as dissociation between two measures. However, when correlations from the same data reflected within-subject preference rank orders between multiple attitude objects, they were substantial (average r = .64). This result suggests that the presence of low correlations between self-report and response time measures in previous studies may be a reflection of methodological aspects of the response time measurement techniques. Property (b) has implications for exploring theoretical questions that require assessment of whether an evaluation is positive or negative (e.g., prejudice), because it allows such classifications in response time measurement to be made for the first time.